The effects of capital requirements on good and bad risk-taking - N. Aaron Pancost; Roberto Robatto (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2019)
We study optimal capital requirement regulation in a dynamic quantitative model in which nonfinancial firms, as well as households, hold deposits. Firms hold deposits for precautionary reasons and to facilitate the acquisition of production inputs. Our theoretical analysis identifies a novel general equilibrium channel that operates through firms' deposits and mitigates the cost of increasing capital requirements. We calibrate our model and find that the optimal capital requirement is 18.7% but only 13.6% in a comparable model in which only households hold deposits. Our novel channel accounts for most of the difference.
Keywords: E21; G21; G32; 330; deposit insurance; capital requirements; idiosyncratic risk; safe assets